1994
DOI: 10.1002/path.1711720104
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of six antibodies for immunohistochemistry of mutant p53 gene product in archival colorectal neoplasms

Abstract: Immunohistochemical detection of intranuclear p53 gene product may indicate mutation of the p53 suppressor gene on chromosome 17p. We used six commercially available antibodies for p53 immunohistochemistry on 19 archival colorectal neoplasms and compared the results with the mutation status of the p53 gene and 17p allelic deletion status. By Friedman's ranking analysis, use of mouse monoclonal antibody DO7 with Target Unmasking Fluid (TUF) for antigen retrieval was the most sensitive and specific procedure (P … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
276
4
10

Year Published

1995
1995
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 474 publications
(309 citation statements)
references
References 27 publications
19
276
4
10
Order By: Relevance
“…Home et al (1996) recently concluded from a panel of MAbs used on breast cancers that pAbi 801 and DO-7 are among the most effective antibodies for IHC in routinely processed material. A similar study on colon cancers revealed that staining with DO-7 after an antigen retrieval method for paraffin sections was the most sensitive and specific procedure (Baas et al, 1994). It is therefore remarkable that Manne et al (1997), who used BP53-12-1 MAb after having established that it gave similar results as pAbI801, reported that the above antigen retrieval procedure abolished the relationship found between p53 positivity and patient survival.…”
Section: Bcl-2 Expressionmentioning
confidence: 94%
See 2 more Smart Citations
“…Home et al (1996) recently concluded from a panel of MAbs used on breast cancers that pAbi 801 and DO-7 are among the most effective antibodies for IHC in routinely processed material. A similar study on colon cancers revealed that staining with DO-7 after an antigen retrieval method for paraffin sections was the most sensitive and specific procedure (Baas et al, 1994). It is therefore remarkable that Manne et al (1997), who used BP53-12-1 MAb after having established that it gave similar results as pAbI801, reported that the above antigen retrieval procedure abolished the relationship found between p53 positivity and patient survival.…”
Section: Bcl-2 Expressionmentioning
confidence: 94%
“…Tumours were assigned to one of three categories: high expression, more than 30% of cancer cells stained; low expression, 1-30% of cancer cells stained; and no expression, 0% cancer cells stained (Baas et al, 1994). Apart from nuclear staining, we also estimated the presence of cytoplasmic staining; staining intensity (SI) was scored as low, intermediate or high.…”
Section: Materials and Methods Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…Non-neoplastic colorectal mucosa, lymphocytes and stromal cells did not show any immunoreactivity. Although detection of p53 overexpression by immunocytochemical means does not necessarily imply a mutant form of the gene, in most (85%) of the cases p53 overexpression coincides with an underlying mutation (Bass et al, 1994).…”
Section: P53 Immunostainingmentioning
confidence: 96%
“…5 Immunohistochemistry for microsatellite analysis of markers hMLH1 and hMSH2 was carried out according to the method of Alexander et al 18 Immunohistochemistry for p53 protein was also performed according to previously published method. 19 Overexpression of p53 protein was considered to be present when more than 50% of the nuclei of tumor cells were strongly stained.…”
Section: Molecules Analysesmentioning
confidence: 99%